Świadomość ubezpieczeniowa studentów w aspekcie postrzegania rynku ubezpieczeniowego - Majewski, Piotr; Walczak, Damian (Studia Oeconomica Posnaniensia, 2013)
One of the key factors affecting the development of the insurance market is insurance awareness. Unfortunately, the perception of this market by both by current and prospective policyholders is not very favourable. Insurance institutions are rated considerably worse than, for example, banks. Among the many factors influencing the attitude of individuals towards the insurance market one of the most important is gender, which probably has, or should have, some influence on preparing an appropriate range of insurance products on offer.